IOT Based Anti-Poaching Sensor System for Commercial Trees - Shruthi, K.R; Jatin, V; Rakshitha, J; Sukruthi, S; Tejaswini, G (International Journal of Computer Sciences and Engineering, 2021)
It is very often heard about the Smuggling of the trees such as Sandal, Teak etc. are taking place throughout the world. These trees are highly expensive as well as less available in the world. Because of huge amount of money involved in selling of such trees, lot of incidents are happening in cutting of trees. In order to avoid the illegal activities on these trees some measures are to be taken. The main objective of the anti-poaching sensor system is to monitor the smuggling of trees and forest fires using flex and flame modules and alerting the user about the same.